1550 Experience from A Level-1 Major Trauma Centre in England of Trauma Epidemiology After Easing of Lockdown Restrictions. (12th October 2021) - Waseem, S; Romann, R; Lenihan, J; Rawal, J; Carrothers, A; Hull, P; Chou, D
Abstract: Aim: The COVID-19 pandemic transformed trauma care. We examined the effect of lockdown easing on trauma presentation and management. Method: Data was retrospectively analysed from Trauma Audit and Research Network (TARN) on patients presenting to one Major Trauma Centre in the East of England with trauma. The first 47 days of lockdown (23 rd March-9 th May 2020, period 1) were compared with the next (10 th May- 26 th June 2020, period 2) and last 47 (27 th June- 13 th August 2020, period 3). Data collected included demographics, mechanism and severity of injury, management, and length of stay. Results: 1, 249 patients were included; 62.2% were male with a mean age of 57.73. Footfall declined in April 2020 compared with 2019 (56 vs 143) but rebounded by May (123 v 120 patients). Road traffic collisions increased over periods 1-3 (18.8% v 23% v 30.1%, p = 0.038); deliberate self-harm (DSH) increased in period 2 compared with 1 and 3 (6.3% v 3.4% v 1.4%, p = 0.03) respectively. The 2020 patient age was younger than 2019, with less trauma relating to alcohol (7.3% v 13.2%, p = 0.009). Compared with 2019 reductions in total length of stay (14.1 v 17.4 days, p = <0.001), critical care length of stay (2.3 v 2.9 days, p = 0.04) and consultant driven care (54.9% v 64.9%, p < 0.001) were noted in lockdown. Conclusions: Our study suggests that after lockdown easing, trauma footfall rapidly rebounded to 2019 levels. This should be acknowledged in resource allocation decisions if future lockdowns are necessitated.